PENGARUH BUDGET PARTICIPATION TERHADAP MANAGERIAL PERFORMANCE MELALUI PERCEPTION OF INNOVATION SEBAGAI VARIABEL INTERVENING - Jemima Sutanto; Josua Tarigan (Business Accounting Review, 2016)
This study aimed to examine the influence of budget participation to managerial performance of corporations. This study used perception of innovation as intervening variable. Samples used in this study were managers working in go public companies in Surabaya region and its surrounding. The hypothesis tested by using SmartPLS 3.0 program. Budget participation in go public companies showed the influence towards managerial performance. There were six indicators used to measure budget participation which were developed by Milani (1975). Whereas, managerial performance were measured by using nine indicators developed by Ahmad and Fatima (2008), namely planning, investigating, coordinating, evaluating, supervising, staffing, negotiating, representing, and overall performance.